Diagnosis of S deficiency in soybean crops: Performance of S and N: S determinations in leaf, shoot and seed - Divito, Guillermo Adrián (2015)
The main areas for soybean production in the world have been recently reported as S-deficient. Chemical analyses of soil samples have not been successful for evaluating the S status of crops. It is generally accepted that plant tissue analyses are better than soil testing for predicting the necessity of S fertilization. Our aims were: (i) to analyze the patterns of S concentration (Sconc), N concentration (Nconc) and N:S ratios in soybean leaf, shoot and seed in response to S availability in soil, (ii) to determine the thresholds for S deficiency, and (iii) to evaluate the performance of the greenness index to assess Sconc and N:S in leaf.Fifteen field experiments were performed during seasons 2012/13 and 2013/14. Sulphur fertilization increased seed yield in 9 out of 15 sites. The critical thresholds for S deficiency were 2.65, 2.06 and 3.93gSkg-1, for leaf, shoot and seed, respectively. For the same plant parts, the N:S critical thresholds were 13.90, 12.18 and 13.50, respectively. The use of N:S better diagnosed the S status than the analysis of Sconc in leaf and shoot. The relative seed yield was weakly associated with Sconc and N:S in seed. We propose the use of N:S in leaf for in-season assessment of S-status. We also found that the greenness index is sensitive to changes in the S status of the plant, which facilitates the diagnosis.